Marriage Problems Because of Disgrace (Study of Book Fiqh Islam wa Adilâtuh and Kitâb al-Nikâh) - Anwar Hafidzi; Norwahdah Rezky Amalia (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2018)
This study discusses the problems of marriage due to the disgrace suffered by one married couple. The purpose of this study was to find out the basis of jurisprudence for those who married because of disgrace, because they had sexually transmitted diseases. The method for this research is library research with descriptive analytic comparative approach, the book of Fiqh al-Islâm wa Adillâtuhby Wahbah al-Zuhaylî and the book of Banjar locality, South Kalimantan Kitab al-Nikâh by Sheikh Muhammad Arsyad al-Banjari. The findings of this study indicate that according to Wahbah al-Zuhaylî, the marriage of a person who has a sexual disease is unlawful even though the desire has required marriage. Meanwhile, according to Muhammad Arsyad al-Banjari only affirmed it, because according to him there is still a gap in maslahah in marriage and family. The academic position of the researcher is more in agreement with al-Banjari's opinion in formulating marriage rules. Comparison of this meeting gives the assumption that policy makers require each bride to check her health to a psychologically and health related hospital to achieve the purpose of marriage. (Penelitian ini membahas tentang problem-problem pernikahan dikarenakan aib yang diderita salah satu pasangan. Tujuan penelitian ini adalah untuk mengetahui dasar fikih bagi mereka yang menikah karena aib pada diri, yaitu mengidap penyakit menular seksual. Metode yang digunakan adalah library research dengan pendekatan descriptive analytic comparative dalam tatanan telaah naskah kitab Fiqh al-Islâm wa Adillâtuh karya Wahbah al-Zuhaylî dan kitab lokal Banjar, Kalimantan Selatan Kitab al-Nikâh karya Syeikh Muhammad Arsyad al-Banjari. Temuan dari penelitian ini menunjukkab bahwa menurut Wahbah al-Zuhaylî, menikahnya seorang yang memiliki penyakit seksual adalah haram hukumnya meskipun hasrat sudah mewajibkan nikah. Sementara menurut Muhammad Arsyad al-Banjari hanya memakruhkannya, dikarenakan melihat masih ada celah maslahah dalam membina rumah tangga. Posisi akademik peneliti lebih menyetujui pendapat al-Banjari dalam merumuskan aturan perkawinan. Perbandingan dari temuaan ini memberikan asumsi bahwa pemangku kebijakan mengharuskan pada setiap mempelai untuk memeriksakan dirinya ke instansi kesehatan terkait psikis dan kesehatannya agar tercapai tujuan dari pernikahan)